Atypical Presentation of Fibroepithelioma of Pinkus: A Case Report and Review of the Literature - Rahmatullah , Fatimah; Jasim, Samar; Abdulqader, Shaymaa; Akram, Nabeeha (AlQalam Journal of Medical and Applied Sciences, 2025)
Fibroepithelioma of Pinkus (FEP) is a slowly growing, low-grade malignant tumor with very low metastatic potential that is considered a distinct variant of basal cell carcinoma (BCC). It usually manifests as sessile or polypoidal lesions on the trunk of middle-aged patients. However, it may present in younger age groups, even in children. In this case, we present a rare case of FEP atypically presenting as a scaly plaque on the lower back for several years in an elderly female who was eventually diagnosed by excisional biopsy and histopathology.